2007
DOI: 10.1590/s0104-11692007000500021
|View full text |Cite
|
Sign up to set email alerts
|

Surgery cancelling at a teaching hospital: implications for cost management

Abstract: This study discusses the problem of surgery cancellation on the economic-financial perspective. It was carried out in the Surgical Center Unit of a school hospital with the objective to identify and analyze the direct costs (human resources, medications and materials) and the opportunity costs that result from the cancellation of elective surgeries. Data were collected during three consecutive months through institutional documents and a form elaborated by the researchers. Only 58 (23.3%) of the 249 cancelled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 6 publications
2
64
0
9
Order By: Relevance
“…In the literature some authors 29 estimated cost by using financial prediction. In Brasil, Perroca et al 2 used bills, factory prices, salaries, vacation salary and taxes to estimate cost. Due to the limited technology in Burkina Faso, we used the tool created by Guiguemdé et al 16 Cost containment through effective and efficient utilisation of resources has become a necessary part of healthcare delivery worldwide.…”
Section: 5 11 22-24mentioning
confidence: 99%
See 3 more Smart Citations
“…In the literature some authors 29 estimated cost by using financial prediction. In Brasil, Perroca et al 2 used bills, factory prices, salaries, vacation salary and taxes to estimate cost. Due to the limited technology in Burkina Faso, we used the tool created by Guiguemdé et al 16 Cost containment through effective and efficient utilisation of resources has become a necessary part of healthcare delivery worldwide.…”
Section: 5 11 22-24mentioning
confidence: 99%
“…Maimaiti et al 11 found a total cost for all surgery cancellations to be around US$ 92 049 with an average cost of US$ 336 per cancelled surgery. In Brasil Perroca et al 2 found a total cost of US$ 3 466.70 with an average cost of US$ 9.50 per patient. Our results showed that the most expensive cancellation to the hospital was ENT procedures (US$ 4 830) for all cancelled cases followed by T&OS (US$ 3 039).…”
Section: 5 11 22-24mentioning
confidence: 99%
See 2 more Smart Citations
“…This same author concluded, the maximum use of surgical capacity favors better management of resources (24) .…”
Section: Resultsmentioning
confidence: 91%